2011
DOI: 10.1126/science.1207313
|View full text |Cite
|
Sign up to set email alerts
|

Altered Telomeres in Tumors with ATRX and DAXX Mutations

Abstract: Chromosome tips seem to be maintained by an unusual mechanism in tumors that have mutations in chromatin remodeling genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
863
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 942 publications
(905 citation statements)
references
References 21 publications
33
863
3
6
Order By: Relevance
“…We used antibodies recognizing the C-terminal of ATRX and DAXX proteins, which have been previously shown to be highly correlated with alternative lengthening of telomeres in pancreatic neuroendocrine tumors. 13 However, theoretically, some point mutations might affect protein function without abolishing protein expression. Therefore, the immunostaining assay might underestimate the frequency of dysfunctional ATRX protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used antibodies recognizing the C-terminal of ATRX and DAXX proteins, which have been previously shown to be highly correlated with alternative lengthening of telomeres in pancreatic neuroendocrine tumors. 13 However, theoretically, some point mutations might affect protein function without abolishing protein expression. Therefore, the immunostaining assay might underestimate the frequency of dysfunctional ATRX protein.…”
Section: Discussionmentioning
confidence: 99%
“…Heaphy et al discovered that alternative lengthening of telomeres status was perfectly correlated with the loss of expression of either α-thalassemia/mental retardation syndrome X-linked (ATRX) or death domain-associated (DAXX) protein in pancreatic neuroendocrine tumors. 13 ATRX and DAXX form a dimer that acts as a histone chaperone to deposit histone variant H3.3 to GC-rich regions of the genome, including the telomeres, and plays important roles in maintaining telomere stability. [14][15][16] It is hypothesized that dysfunction of the dimer leads to telomere instability, increased telomere homologous recombination, and ultimately, alternative lengthening of telomeres.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also identified ATRX mutations in a number of cancers, including pancreatic neuroendocrine tumors and glioblastoma multiforme, suggesting that ATRX function is critically important to numerous aspect of cellular homeostasis (Heaphy et al, 2011;Schwartzentruber et al, 2012). Interestingly, Rett syndrome, a neurodevelopmental autism spectrum disorder caused by mutations in the MECP2 gene (Amir et al, 1999), has been indirectly linked to ATRX syndrome, although the direct functional consequences of disrupting ATRX/MeCP2 interactions in brain remain unclear.…”
Section: Atrx: a Critical Regulator Of Chromatin State And Histone Dymentioning
confidence: 99%
“…PanNETs with DAXX/ATRX mutations almost always have the ''alternative lengthening of telomeres'' (ALT?) phenotype [133,134]. Other genes targeted in PanNETs include genes coding for members of the phosphatidylinositol 3 0 -kinase (PI3K)-AKT-mTOR pathway.…”
Section: Pancreatic Neuroendocrine Tumorsmentioning
confidence: 99%